Atmosphere-Mediated Superhydrophobicity of Rationally Designed Micro/Nanostructured Surfaces - Yan, Xiao; Huang, Zhiyong; Sett, Soumyadip; Oh, Junho; Cha, Hyeongyun; Li, Longnan; Feng, Lezhou; Wu, Yifan; Zhao, Chongyan; Orejon, Daniel; Chen, Feng; Miljkovic, Nenad (ACS nano, 2019)
Superhydrophobicity has received significant attention over the past three decades owing to its significant potential in self-cleaning, anti-icing and drag reduction surfaces, energy-harvesting devices, antibacterial coatings, and enhanced heat transfer applications. Superhydrophobicity can be obtained via the roughening of an intrinsically hydrophobic surface, the creation of a re-entrant geometry, or by the roughening of a hydrophilic surface followed by a conformal coating of a hydrophobic material. Intrinsically hydrophobic surfaces have poor thermophysical properties, such as thermal conductivity, and thus are not suitable for heat transfer applications. Re-entrant geometries, although versatile in applications where droplets are deposited, break down during spatially random nucleation and flood the surface. Chemical functionalization of rough metallic substrates, although promising, is not utilized because of the poor durability of conformal hydrophobic coatings. Here we develop a radically different approach to achieve stable superhydrophobicity. By utilizing laser processing and thermal oxidation of copper (Cu) to create a high surface energy hierarchical copper oxide (CuO), followed by repeatable and passive atmospheric adsorption of hydrophobic volatile organic compounds (VOCs), we show that stable superhydrophobicity with apparent advancing contact angles ≈160° and contact angle hysteresis as low as ≈20° can be achieved. We exploit the structure length scale and structure geometry-dependent VOC adsorption dynamics to rationally design CuO nanowires with enhanced superhydrophobicity. To gain an understanding of the VOC adsorption physics, we utilized X-ray photoelectron and ion mass spectroscopy to identify the chemical species deposited on our surfaces in two distinct locations: Urbana, IL, United States and Beijing, China. To test the stability of the atmosphere-mediated superhydrophobic surfaces during heterogeneous nucleation, we used high-speed optical microscopy to demonstrate the occurrence of dropwise condensation and stable coalescence-induced droplet jumping. Our work not only provides rational design guidelines for developing passively durable superhydrophobic surfaces with excellent flooding-resistance and self-healing capability but also sheds light on the key role played by the atmosphere in governing wetting.